The association between time of in hospital cardiac arrest and mortality; a retrospective analysis of two UK databases - McGuigan, PJ; Edwards, J; Blackwood, B; Dark, P; Doidge, JC; Harrison, DA; Kitchen, G; Lawson, I; Nichol, AD; Rowan, KM; Shankar-Hari, M; McAuley, DF (Elsevier, 2023)
Aims: The incidence of in hospital cardiac arrest (IHCA) varies throughout the day. This study aimed to report the variation in incidence of IHCA, presenting rhythm and outcome based on the hour in which IHCA occurred.